Laclos no Brasil: análise crítica das traduções contemporâneas de Les liaisons dangereuses - Laís Zampol Dell’ Antonia (2019)
The research aims to critically analyse two Brazilian Portuguese translations As Ligações Perigosas by Fernando Cacciatore Garcia and As Relações Perigosas by Dorothée de Bruchard. Both books are translations of the epistolary libertine French novel Les Liaisons Dangereuses originally published in 1782 by Choderlos de Laclos. The study was based on Antoine Berman’s ideas of Translation and intended to identify the following variables: the dominant choices of translation, the inherent difficulties encountered when translating an 18th-century romance, and the proposed solutions to these dilemmas. Structural, Lexical and Semantic elements were examined in order to evaluate the effectiveness of the Bermanian thought. Inversely, the translation’s validity was also analysed according to Berman’s conception ‘fidelity to the letter’. It was observed the presence of linguistic, historical and cultural differences between the original novel and its translation. Eventually, this finding can indicate infidelity from the translator. Therefore, the Bermanian approach application has shown to be feasible. Thus, the similarity between a translation and its original text is a choice of the translator.